The Space-Time CE/SE Method for Solving Reduced Two-Fluid Flow Model (Communications in Computational Physics, 2012)
The space-time conservation element and solution element (CE/SE) methodis proposed for solving a conservative interface-capturing reduced model of compressible two-fluid flows. The flow equations are the bulk equations, combined with massand energy equations for one of the two fluids. The latter equation contains a sourceterm for accounting the energy exchange. The one and two-dimensional flow models are numerically investigated in this manuscript. The CE/SE method is capable toaccurately capture the sharp propagating wavefronts of the fluids without excessivenumerical diffusion or spurious oscillations. In contrast to the existing upwind finitevolume schemes, the Riemann solver and reconstruction procedure are not the building block of the suggested method. The method differs from the previous techniquesbecause of global and local flux conservation in a space-time domain without resortingto interpolation or extrapolation. In order to reveal the efficiency and performance ofthe approach, several numerical test cases are presented. For validation, the results ofthe current method are compared with other finite volume schemes.